LIOFeron®TB/LTBI: A novel and reliable test for LTBI and tuberculosis. (February 2020) - Della Bella, Chiara; Spinicci, Michele; Alnwaisri, Heba F. Mustafa; Bartalesi, Filippo; Tapinassi, Simona; Mencarini, Jessica; Benagiano, Marisa; Grassi, Alessia; D'Elios, Sofia; Troilo, Arianna; Abilbayeva, Arailym; Kuashova, Dinara; et al.
Graphical abstract: Highlights: LIOFeron®TB/LTBI is an IGRA ideated to assess the T cell response in MTB infection. It contains ESAT-6, CFP-10 and Ala-DH, a useful tool for LTBI diagnosis. The accuracy of MTB infection diagnosis of LIOFeron®TB/LTBI assay is high. LIOFeron®TB/LTBI shows higher sensitivity than QFT®-TB Gold Plus in LTBI detection. Abstract: Objectives: High accuracy diagnostic screening tests for tuberculosis (TB) are required to improve the diagnosis of both active TB and latent Mycobacterium tuberculosis (MTB) infection (LTBI). The novel IGRA LIOFeron®TB/LTBI assay was tested and its accuracy was compared to the QuantiFERON®-TB Gold Plus assay. Methods: A total of 389 subjects were enrolled in two cohorts and classified as healthy, active TB or LTBI persons. The blood of all the patients was tested with LIOFeron®TB/LTBI assay, containing MTB alanine dehydrogenase, able to differentiate active TB from LTBI diagnosis. The results obtained with both IGRAs, performed on the same 250 samples, were finally compared. Results: The two assays demonstrated an excellent concordance of their results with patients' diagnosis of MTB infection. ROC analysis for QuantiFERON®-TB Gold Plus showed sensitivity and specificity respectively of 98% and 97% in diagnosing active TB patients and 85% and 94% in diagnosing LTBI subjects. LIOFeron®TB/LTBI assay showed sensitivity and specificity respectively of 90% and 98% in diagnosing active TB patients and 94% and 97% in diagnosing LTBI subjects. Conclusions: The two IGRAs displayed the same high accuracy in diagnosing MTB infection/TB disease, and LIOFeron®TB/LTBI assay demonstrated higher sensitivity than QuantiFERON®-TB Gold Plus test in LTBI detection.